Viral infection and its impact on fertility, medically assisted reproduction and early pregnancy – a narrative review - Piotr Laudański; Aleksandra Zyguła; Adam Czyżyk; Katarzyna Olszak-Wasik; Damian Warzecha; Cezary Wojtyła; Rafał Kurzawa (Reproductive Biology and Endocrinology)
Abstract Viral infections can significantly affect the physiopathology of reproductive organs, leading to fertility problems, reducing the success rates of assisted reproductive technologies, and negatively impacting pregnancy. This review aims to summarize the current evidence on viral pathogens that are either suspected or confirmed to play a role in reproductive medicine and their effects on early pregnancy. For instance, viral hepatitis and human immunodeficiency virus can decrease sperm quality. Human papilloma virus infection in men appears to cause infertility, while herpesviruses pose a greater risk to fetuses rather than to fertility. The Zika virus disrupts early embryo development, necessitating a delay in conception for those suspected or confirmed to be infected. The effects of SARS-CoV-2 on reproduction are still unclear. Rubella and cytomegalovirus can cause serious congenital defects, making pre-conception screening essential, and a Rubella vaccine is recommended. More rigorous studies are needed to clarify the roles of various infectious agents, enhance fertility treatments, and improve pregnancy outcomes while reducing complications.